Pemetaan Daerah Aktivitas Perikanan Berbasis Data AIS - Busaina, Ladisa; Utami, Nandya Rezky; Pramana, Setia; Krismawati, Dewi (Seminar Nasional Official Statistics, 2024)
Digital development brings significant changes in data collection and processing, with big data becoming the main source of official statistics. BPS has been using big data since 2015 for more accurate analysis and statistics. Automatic Identification System (AIS) data, an automated ship navigation system, effectively monitors ship movements and is used for official statistics, improving accuracy and reducing human error. However, monitoring of Indonesia's marine activities is still not optimal, as seen from the low contribution of the fisheries sector to GDP and indications of overfishing due to illegal fishing activities (IUU). The use of AIS is important for monitoring illegal activities, but data quality is often low. Data quality assurance through preprocessing is needed. This research will map fisheries activity areas in the waters around Papua Island using AIS data and the DBSCAN algorithm to cluster fishing vessels, in order to improve monitoring of fisheries activities in Indonesia.